Sunni to Shia Conversion in Indonesia - Siti Syamsiyatun; Dicky Sofjan; Imran Imran (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Since the Iranian Islamic revolution led by Imam Khomeini, Shia and its community have received a lot of attention as a research subject. This paper aims to examine how the phenomenon of conversion from Sunni-Shia in Indonesia. What underlies the choice to convert even with the consequence that conversion to Shia has the potential to cause psychological, economic, social and political tensions. This research was conducted in four cities in Indonesia, namely Jakarta, Bandung, Yogyakarta and Makassar. These cities are used to represent Indonesia. The results of the study show that there are at least four 'gates' which are the main arguments in their decision to convert from Sunni to Shia. These gates are 'philosophy', 'history', 'Irfan/Sufism', and 'fiqh gates'. The typology of encounters through the four doors is a strong typology that I encountered in my research. most people who convert from Sunni to Shia usually pass through one or several gates that become milestones for their acceptance of Shia.